Expulsion Methylene Blue MB Dye from Aqueous Solution by Using Activated Camel Thorn (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The chance of camel thistle squander as eco-accommodating, accessible, and monetary adsorbent for adsorption methylene blue color from its watery arrangement was analyzed by utilizing clump and section framework. All experiments of  the batch were achieving with modification camel thorn waste dye concentration 50 mg/L, pH6.5, Temp 25 oC.Materials and Methods: Camel thorn (CT) waste were collected from AL-Mahaweel region, this region situated in Babylon city/Iraq. The waste were direct washed with running water tap to release all impurities, and rinsed with distilled water for 4 times, after then it dried under sunlight, and then in oven under 50 oC for two hours. The dried (CT) waste were ground and sieved BSS-60 mesh size particleResults: Methylene Blue(MB) dye was examined to remove  from the aqueous solution  by adsorption on the camel thorn waste added to the acidic adsorbent modification, thermal adsorbent modification on the decolonization dye efficiency was studies were investigated with the similar working condition contact time (2-90 min).Conclusion: The current discoveries created the impression that the that normal adsorbent, camel thistle squander is altogether appropriate for the depolarization of methylene blue color from its watery arrangement. The outcomes show that the balance isotherm for the two modules that utilized in this work are of good kind, for being curved vertical